CLOUD COMPUTING INFRASTRUCTURE DESIGN WITH OPENSTACK ON LOCAL NETWORK USING VIRTUALBOX - Budi Santoso, Septian; Sari Hasibuan, Mila Nirmala; Akbar, Ali (Sean Institute, 2022)
The development of cloud computing technology that is mushrooming in the world, as well as in Indonesia, is one of the causes of revolutionary changes in trends that have made many industries / organizations / agencies / institutions / companies adopt and implement them. To face the challenges of these technological developments, the Indonesian Business Polytechnic Murni Sadar Campus Pematangsiantar City is one of the private universities engaged in the world of education ready to face these changing trends to take part in educating the nation's children. The challenge of the development of cloud computing technology is to design a system with openstack as the software platform for the cloud, the ubuntu server as the operating system uses virtualization with virtualbox in order to obtain a capable system before being implemented to a physical server in the laboratory room in order to increase the efficiency of lectures. aimed at meeting the needs for practicum activities for students at the PBI campus so that they can taste and explore cloud computing technology so that they have additional knowledge to face the industrial revolution 4.0.